Mirror-Image Arachnoid Cysts in a Pair of Monozygotic Twins: A Case Report and Review of the Literature - Zhou, Jing-Yi (Ivyspring International Publisher, 2011)
Mirror-imaging of arachnoid cysts (ACs) in monozygotic twins (MZ) is extremely rare. We describe a pair of MZ who developed mirror-imaging of ACs in the temporal fossas, and we also review the literature. Brain computer tomography (CT) and Magnetic Resonance Imaging (MRI) of the MZ revealed mirror-imaging of vast lesions of cerebrospinal fluid intensity in their temporal fossas. This is the second ever report of such a case according to the available literature. Unlike the prior case, our patients were 14 months, which is a much younger age than the patients of the previous report. Consequently, our case is better in supporting a genetic origin in the pathogenesis of AC. The findings in our case indicate that early neuroimaging is mandatory in the counterpart of the symptomatic patient with AC, irrespective of the absence of symptoms.